Electrochemical corrosion of a glassy carbon electrode - Yi, Youngmi; Weinberg, Gisela; Prenzel, Marina; Greiner, Mark; Heumann, Saskia; Becker, Sylvia; Schlögl, Robert (Catalysis today, 2017)
[Display omitted] •Glassy carbon is not electrochemically inert.•At high anodic potentials oxidation of water and carbon electrodes occurs simultaneously.•Different corrosion behavior of glassy carbon in different pH electrolytes was observed.•Carbon oxidation in acidic media forms surface oxides.•Carbon in alkaline media dissolves during the electrochemical oxidation. Glassy carbon is widely used in electrochemistry due to its properties of high temperature resistance, hardness, low density and low electrical resistance. The present study focuses on the chemical resistance under electrochemical oxidative conditions, which occur under oxygen-involving reactions like oxygen reduction reaction (ORR) and oxygen evolution reaction (OER). The electrochemical performance of glassy carbon investigated in alkaline, neutral and acidic media reveal the same chemical processes during the OER but showing different degradation mechanism. The electrochemical signature of the corrosion in different media could be directly associated with the formation of oxygen functional groups determined by spectroscopic methods like Raman, infrared (IR) and x-ray photoelectron spectroscopy (XPS). The morphology change of the carbon surface caused by carbon oxidation was investigated by microscopy. A rough surface was obtained in the acidic case, whereas dents were seen in alkaline media. It is assumed that the glassy carbon electrode in acidic media degrades by forming surface oxides by acid catalyzed process leading to ring opening in the graphitic structure and therefore oxidation in the bulk. In alkaline media OH radicals preferentially react with alkyl site chains, leading to oxidation of the edges of carbon layers until they become hydrophilic and dissolve.